PENGARUH LINGKUNGAN KELUARGA DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS X SMA NEGERI 10 MEDAN TAHUN AJARAN 2025/2026 - Marsanda Hutagalung; Charles Fransiscus Ambarita (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This research is motivated by the low learning achievement of class X students in Economics at SMA Negeri 10 Medan, many of whom have not yet reached the Minimum Completion Criteria (KKM). The purpose of this study is to determine the influence of the family environment and learning facilities on students’ achievement in Economics. A quantitative approach with an ex-post facto design was used. The population comprised 252 class X students, with a sample of 154 respondents selected by simple random sampling. Data were collected through observation, interviews, documentation, and Likert-scale questionnaires. Data analysis used multiple linear regression. The results show the regression equation Y = a + b1X1 + b2X2. Partial hypothesis tests indicate the family environment has a positive and significant effect on Economics achievement (tcount > ttable; p < 0.05). Partially, learning facilities also have a positive and significant effect (tcount > ttable; p < 0.05). Simultaneous testing shows both variables jointly have a positive and significant effect on Economics achievement (Fcount > Ftable; p < 0.05). The combined influence of family environment and learning facilities on Economics achievement is 62%, while the remaining 38% is explained by other variables not examined in this study. Thus, there is a positive and significant influence of family environment and learning facilities on the Economics achievement of grade 10 students at SMA Negeri 10 Medan. Keywords: Family Environment, Learning Facilities, Economics Learning Achievement   Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya prestasi belajar siswa pada mata pelajaran Ekonomi kelas X di SMA Negeri 10 Medan yang masih banyak belum mencapai Kriteria Ketuntasan Minimal (KKM). Tujuan penelitian ini adalah mengetahui pengaruh lingkungan keluarga dan fasilitas belajar terhadap prestasi belajar ekonomi siswa. Pendekatan kuantitatif digunakan dengan jenis ex-post facto. Populasi 252 siswa kelas X, sampel 154 responden menggunakan simple random sampling. Pengumpulan data melalui observasi, wawancara, dokumentasi, dan angket skala Likert. Analisis data menggunakan regresi linear berganda. Hasil analisis menunjukkan persamaan regresi Y = a + b1X1 + b2X2. Uji hipotesis parsial menunjukkan lingkungan keluarga berpengaruh positif dan signifikan terhadap prestasi belajar ekonomi (thitung > ttabel; sig. < 0,05). Secara parsial fasilitas belajar juga berpengaruh positif dan signifikan (thitung > ttabel; sig. < 0,05). Uji simultan menunjukkan kedua variabel berpengaruh positif dan signifikan terhadap prestasi belajar ekonomi (Fhitung > Ftabel; sig. < 0,05). Pengaruh lingkungan keluarga dan fasilitas belajar terhadap prestasi belajar ekonomi sebesar 62%, sedangkan 38% dipengaruhi variabel lain yang tidak diteliti. Dengan demikian, terdapat pengaruh positif dan signifikan antara lingkungan keluarga dan fasilitas belajar terhadap prestasi belajar ekonomi siswa kelas X SMA Negeri 10 Medan. Kata Kunci: Lingkungan Keluarga, Fasilitas Belajar, Prestasi Belajar Ekonomi